Focus on alcohol - Grace, Catherine O'Neill 1950-; Neuhaus, David (Frederick, MD Twenty-first Century Books, 1990)
Discusses the history, use, and dangers of alcohol, the problems of alcoholism, and coping with the pressures to drink.
Keywords: Alcoholism -- Juvenile literature. -- United States